1984
DOI: 10.1128/aac.26.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of 1,292 isolates of the Bacteroides fragilis group in the United States: comparison of 1981 with 1982

Abstract: A susceptibility survey of 537 strains of the Bacteroidesfragilis group from eight centers in the United States was continued at the Tufts New England Medical Center in 1982. The results were compared with those of 755 organisms analyzed in 1981. Nine antimicrobial agents were tested by an agar dilution method. The respective percentages of resistance for 1981 and 1982 were as follows (%): cefoxitin, 8 and 10; moxalactam, 22 and 12; cefotaxime, 54 and 48; cefoperazone, 57 and 54; piperacillin, 12 and 7; clinda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
33
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 8 publications
(8 reference statements)
6
33
1
Order By: Relevance
“…Cefmetazole was less active; the MIC for 90% of the strains was 64 p,g/ml. As reported previously (3,8,16, 26) (Table 2).…”
supporting
confidence: 73%
See 3 more Smart Citations
“…Cefmetazole was less active; the MIC for 90% of the strains was 64 p,g/ml. As reported previously (3,8,16, 26) (Table 2).…”
supporting
confidence: 73%
“…Cefmetazole was less active; the MIC for 90% of the strains was 64 p,g/ml. As reported previously (3,8,16, 26) (Table 2).The results of this study indicate that several of the new beta-lactam agents are effective in vitro against the B. fragilis group. As expected, chloramphenicol and metronidazole were uniformly effective against all 94 isolates.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…The Anaerobe Working Group for the National Committee for Clinical Laboratory Standards (NCCLS) recommends that susceptibility testing of the B. fragilis group be done with a distribution of test isolates to approximate the species distribution normally isolated from infections (7). Several multicenter susceptibility studies have shown that the B. fragilis species comprises 58 to 63% of isolates (1,5,6,17). Such distribution rates have been relatively evident in studies reported during the 1980s and early 1990s.…”
mentioning
confidence: 93%